2015
DOI: 10.1177/0300060514559791
|View full text |Cite
|
Sign up to set email alerts
|

Addition of all-trans-retinoic acid to omeprazole and sucralfate therapy improves the prognosis of gastric dysplasia

Abstract: Objective: To investigate the efficacy of all-trans retinoic acid (ATRA) in human gastric dysplasia. Methods: In this double-blind study, patients with precancerous gastric dysplasia with or without intestinal metaplasia (IM) received either conventional treatment consisting of omeprazole and sucralfate (control group) or conventional treatment plus ATRA. Gastric mucosal biopsies were performed before and after drug treatment and were analysed histologically; expression of retinoblastoma (Rb) protein and HER2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
(76 reference statements)
1
6
0
Order By: Relevance
“…We have demonstrated that treatment with ENT reduces HER2 expression via degradation of chaperone protein hsp90 [8]. ATRA has also been shown to downregulate HER2; Jin et al showed that treatment with ATRA reduced HER2 expression in gastric dysplasia [17]. This data supports findings from Grunt and colleagues who observed downregulation of HER2 in breast cancer cell lines SkBR3 and BT474 following treatment with ATRA; this downregulation was postulated to be through inhibition of the transcription factor AP-1 [18].…”
Section: Discussionsupporting
confidence: 86%
“…We have demonstrated that treatment with ENT reduces HER2 expression via degradation of chaperone protein hsp90 [8]. ATRA has also been shown to downregulate HER2; Jin et al showed that treatment with ATRA reduced HER2 expression in gastric dysplasia [17]. This data supports findings from Grunt and colleagues who observed downregulation of HER2 in breast cancer cell lines SkBR3 and BT474 following treatment with ATRA; this downregulation was postulated to be through inhibition of the transcription factor AP-1 [18].…”
Section: Discussionsupporting
confidence: 86%
“…ATRA, a therapy that has transformed the treatment of APL, has been shown to inhibit gastric cancer in cancer cell models and even in human patients, with anticancer mechanisms being traditionally attributed to activation of retinoic acid receptor (RARs) or retinoid X receptor (RXRs) . However, our recent mechanism‐based drug screens have surprisingly identified that ATRA is a Pin1 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Although a small study of 182 cases has shown Pin1 overexpression in human gastric cancer, the role of Pin1 in the development and treatment of gastric cancer is still unknown. Moreover, although ATRA has been shown to inhibit gastric cancer in cancer cell models and even in human patients, it is not known whether Pin1 plays any role in mediating its anticancer activity in gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Jin J et al showed that patients with gastric dysplasia treated with omeprazole and sucralfate, associated to ATRA, presented a better attenuation of their dysplasia (68% vs. 37%) compared to patient treated with omeprazole and sucralfate alone. This was accompanied with an increased expression of the tumor suppressor pRb and a decreased expression of HER2 oncogenic receptor in patient’s gastric mucosa [ 99 ].…”
Section: Atra On Gc Modelsmentioning
confidence: 99%